Enter to the New Ukrainian literature and the Skovoroda’s key (according to the lecture-conversation "From Skovoroda to Shevchenko", presented at the literary and music festival "Pyatiy Kharkiv" on September 23, 2022) - Chopyk, Rostyslav (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2022)
The significance of G.Skovoroda for the formation of New Ukrainian literature was underestimated for a long time even by its leading figures (T.Shevchenko, P. Kulish). First of all, because of the “book language” of the writings of the wise man; the fact that most of them have not been published; and also active attempts by some Russian and pro-Russian figures (for example, A. Hashdeu) to appropriate it for Russian culture. The situation began to change after the publication of the full collection of G.Skovoroda’s works, edited by D. Bagaliya (1894). A number of heuristic studies appeared (O. Rusov, S. Yefremov, M. Hrushevskyi, M. Plevako), but Stalin’s repressions stopped further progress in this direction. Until it was restored by L. Ushkalov ("Baroque Sources of New Ukrainian Literature", "Skovoroda and Ukraine", etc.). The aim of the article is to develop the work of the predecessors, enriching it with new own observations, like relation Skovorodynstvo (Skovoroda’s philosophy) and the author of Natalka Poltavka, which is a "variation on the theme of Skovoroda’s ’Poor (Pious) Lark’" (according to L. Ushkalov). The burlesque-travesty style of "Aeneid", which is a "smart joke" about non-kinship (the leitmotif of "Fables of Kharkiv"), corresponds to Skovoroda’s outlook. This includes not only the direct influence of Skovoroda on the representatives of New Ukrainian literature, but also the painting style as a marker of their Ukrainian worldview (the starting impulse of T. Shevchenko’s poetic work at the time of the redemption from serfdom, when the realization of the painterly — kindred — potential was under threat) and, accordingly, anti-kinship — as an indicator of anti-Ukrainianism. For example, in late, already in crisis, M. Gogol, renounced himself ("Selected places of correspondence with friends"). Skovorodynstvo sets the main development of the New Ukrainian literature, and therefore, the perspective of the study of the "literature-centric" Ukrainian national identity, the formation of which began with the "Key to Everything: Know Yourself" by the author of the book "The Key to Everything: discover Yourself".